THE IMPORTANCE OF THE STATE IN THE TRANSFORMATION OF THE ECONOMIC MARKET MODELS - Marina Rybasova (Вестник Северо-Кавказского федерального университета, 2022)
The article presents a study of the Russian economy in major market models taking into account the inluence of modern development factors: motivation business activities to improve strategic planning, cross-sectoral regional cooperation, the transition to innovation type of socio - economic development. The author noted that Russia needs to wriggle out of almost hopeless situation and response to the sanctions, the metropolis of the new model of economic growth. To the country has made a real step in the direction of the sixth sector of the economy, you must implement it system changes that would have affected the fundamental basis of society.